1995
DOI: 10.1007/bf00197752
|View full text |Cite
|
Sign up to set email alerts
|

Androgen increases olfactory receptor response to a vertebrate sex pheromone

Abstract: Although it is well known that responses to ethologically-relevant odors are influenced by endocrine factors, it has not been clear whether these hormonal effects might be mediated at the level of the peripheral sensory neurons. During an investigation of hormonal pheromones in South-East Asian Cyprinids, we observed that in adult male Puntius schwanenfeldi, an androgendependent sex character was correlated with electro-olfactogram response to a putative sex pheromone (15-keto-prostaglandin-F2a). As secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 37 publications
8
46
1
Order By: Relevance
“…The androgen treated males paid more attention to the female compared with the castrated controls. Implantation and injection experiments with various fish species of different taxonomic groups have revealed that male prespawning behaviour is in some species dependent of gonadal androgens (Liley & Stacey 1983;Borg 1987) and in a cyprinid fish (Puntius schwanenfeldi) androgen treatment of males increased their olfactory sensitivity to the putative hormone pheromone 15-keto-prostaglandin-F 2h (Cardwell et al 1995). No such relationships have yet been shown in salmonids.…”
Section: Discussionmentioning
confidence: 99%
“…The androgen treated males paid more attention to the female compared with the castrated controls. Implantation and injection experiments with various fish species of different taxonomic groups have revealed that male prespawning behaviour is in some species dependent of gonadal androgens (Liley & Stacey 1983;Borg 1987) and in a cyprinid fish (Puntius schwanenfeldi) androgen treatment of males increased their olfactory sensitivity to the putative hormone pheromone 15-keto-prostaglandin-F 2h (Cardwell et al 1995). No such relationships have yet been shown in salmonids.…”
Section: Discussionmentioning
confidence: 99%
“…In two fish species, hormonal status influences male sensitivity to female-produced sex pheromones. Adult male Puntius schwanenfeldi increase peripheral nervous system sensitivity to pheromone with increased androgen titer (Cardwell et al, 1995) whereas endocrine effects on the central nervous system mediate pheromone responsiveness in the goldfish Carassius auratus (Sorensen et al, 1987). Male hamsters respond to sex pheromone only if a threshold level of testosterone occurs in the brain (Wood and Swann, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…mature males have higher sensitivity to (a) component(s) in female urine than females themselves. Thus, the process of sexual maturation may influence the expression of olfactory receptor genes in the olfactory epithelium in the sole, as has been shown in the eel (Churcher et al, 2015), and in cyprinids, olfactory sensitivity is increased by androgens (Belanger et al, 2010;Cardwell et al, 1995;Ghosal and Sorensen, 2016). It is likely, therefore, that during sexual maturation, increased circulating sex steroids evoke a differential expression of pheromone receptors in the olfactory epithelium.…”
Section: Discussionmentioning
confidence: 88%